2019
DOI: 10.3389/fphys.2019.00145
|View full text |Cite
|
Sign up to set email alerts
|

QRS-T Angle Predicts Cardiac Risk and Correlates With Global Longitudinal Strain in Prevalent Hemodialysis Patients

Abstract: Background: Cardiovascular disease is the commonest cause of death in hemodialysis (HD) patients but accurate risk prediction is lacking. The spatial QRS – T angle is a promising electrophysiological marker for sudden cardiac death risk stratification. The aim of this study was to assess the prognostic value of spatial QRS-T angle derived from standard 12 lead electrocardiograms (ECG) and its association with echocardiographic parameters in HD patients. Methods: This prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Abnormalities in depolarization mirror structural abnormalities, while those in repolarization reflect changes in regional action potential duration and the direction of repolarization sequence associated with electrical instability and SCD. QRS-T angle is an established marker of global repolarization heterogeneity, possibly related to underlying structural and functional myocardial abnormalities [ 3 , 6 8 , 11 , 14 16 , 18 ]. In our study, abnormal QRS-T angle was found in 30% of HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in depolarization mirror structural abnormalities, while those in repolarization reflect changes in regional action potential duration and the direction of repolarization sequence associated with electrical instability and SCD. QRS-T angle is an established marker of global repolarization heterogeneity, possibly related to underlying structural and functional myocardial abnormalities [ 3 , 6 8 , 11 , 14 16 , 18 ]. In our study, abnormal QRS-T angle was found in 30% of HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…A pubmed search using the terms HRV and dialysis returns 122 studies with the first one published already in 1986 (Forsstrom et al, 1986). Abnormal HRV indices have been associated with all cause (Hayano et al, 1999; Oikawa et al, 2009; Suzuki et al, 2012; Chen et al, 2016; Ng et al, 2017; Poulikakos et al, 2018) and cardiovascular mortality (Hayano et al, 1999; Fukuta et al, 2003; Oikawa et al, 2009; Chen et al, 2016) in east Asian HD patients and in one small study including predominantly Caucasian HD patients (Skampardoni et al, 2018a). Depressed HRV has also been associated with all cause (Pei et al, 2015; Chiang et al, 2016) and cardiovascular (Hayano et al, 1999) mortality in east Asian patients receiving peritoneal dialysis.…”
Section: Non-invasive Electrophysiology In Dialysis Patientsmentioning
confidence: 99%
“…The QRS-T angle is calculated numerically, is reproducible (Poulikakos et al, 2013; Hnatkova et al, 2017) and thus suitable for risk stratification purposes. A larger QRS-T angle has been shown to predict SCD (de Bie et al, 2013b; Tereshchenko et al, 2016), cardiovascular mortality (Skampardoni et al, 2018a) and all cause mortality (Tereshchenko et al, 2016; de Bie et al, 2013b; Poulikakos et al, 2018) in different cohorts of predominantly African (Tereshchenko et al, 2016) and Caucasian (Sallam et al, 2015; Poulikakos et al, 2018; Skampardoni et al, 2018a) dialysis patients. However, one study in 325 Taiwanese HD patients (Lin et al, 2007) did not find a significant association between magnitude of QRS-T angle and outcomes.…”
Section: Non-invasive Electrophysiology In Dialysis Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…T wave axis has also been shown to be a strong predictor of cardiac morbidity, cardiac mortality and all-cause mortality [3] [4] [5] [6]. QRS-T angle, which is the angle between QRS axis and T wave axis, is a strong predictor of cardiac morbidity, cardiac mortality and all-cause mortality [4] [7] [8]. Since QRS-T angle is the difference between the QRS axis and T wave axis [9] QRS-T angle indirectly indicates the prognostic value of QRS axis.…”
Section: Introductionmentioning
confidence: 99%